The Early Life of Mark Rutherford (W. Hale White) - White, William Hale, 1831-1913 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Early Life of Mark Rutherford (W. Hale White)" by William Hale White is an autobiographical account written in the early 20th century, reflecting on the author's formative years during the Victorian period. This work is not just a personal memoir; it delves into the social, political, and cultural dynamics of the time, as experienced by White. The book serves as a nostalgic exploration of White's early life, the influences that shaped his identity, and the broader Victorian society in which he grew up. In this engaging narrative, White recounts significant moments from his childhood in Bedford, including family relations, early education, and the burgeoning influences of literature and political thought. He reflects on his family's dynamics, the educational systems of his youth, and his encounters with notable figures of the time, such as John Ruskin and his uncle, who significantly impacted his outlook on life. Throughout the memoir, White captures the essence of his experiences$1 (Bincluding his spiritual journey, the tension between Dissent and orthodoxy in religion, and the emotional weight of familial expectations$1 (Ball presented through a lens of rich detail that paints a vivid picture of both personal and societal change in Victorian England. (This is an automatically generated summary.)s
Release date is 2005-01-01
Transcribed from the 1913 Oxford University Press by David Price
Keywords: White, William Hale, 1831-1913 -- Childhood and youth